(untitled) (Reumatismo, 2006)
Objective. To investigate the Italian version of HAQ-DI (Health Assessment Questionnaire Disability Index) in systemic sclerosis (SSc). Methods. 121 SSc patients, satisfying ACR criteria for the classification of this disease and consecutively admitted to a tertiary Unit, were invited to participate to the study. The Italian version of HAQ-DI, as validated in rheumatoid arthritis, was administered to each of them. The relationships between this parameter and the following disease aspects: disease subset, wide extent of skin sclerosis, joint contractures, myopathy, active digital ulcers, were investigated. Results. HAQ-DI resulted to be 0.772±0.074 (mean±SE) Statistically significant differences in HAQ-DI scores were detected between patients with and respectively without wide extent of skin sclerosis (ie modified Rodnan skin score >14) (1.158±0.176 vs 0.652±0.076; P<0.001), joints contractures (0.839±0.076 vs 0.159±0.147; P<0.001), myopathy (1.875±0.184 vs 0.656±0.071; P<0.001), digital ulcers (1.047±0.135 vs 0.680±0.109; P=0.006). Conclusions. Our data support the validity of the Italian version of HAQ-DI in SSc.